Type 2 fimbrial lectin-mediated phagocytosis of oral Actinomyces spp. by polymorphonuclear leukocytes. - Sandberg, A L (1986)
Phagocytosis of Actinomyces viscosus T14V and A. naeslundii WVU45 by human polymorphonuclear leukocytes in the absence of antibody or complement was mediated by the lectin associated with the type 2 fimbriae of these bacteria. This effect was markedly enhanced by exogenous sialidase, an enzyme also secreted by these actinomyces. Since sialidase treatment of the bacteria did not result in increased phagocytosis, this enzyme presumably acts by unmasking receptors for the fimbrial lectin on phagocytic cells. The viability of A. viscosus T14V, which possesses type 1 and type 2 fimbriae (1+ 2+), and A. naeslundii WVU45, which possesses only type 2 fimbriae (2+), was decreased by at least 98% following incubation with polymorphonuclear leukocytes in the presence of sialidase. Entirely analogous findings were obtained with a 1- 2+ mutant of A. viscosus T14V. In contrast, the phagocytosis of 1+ 2- and 1- 2- mutants of A. viscosus T14V and a 2- mutant of A. naeslundii WVU45 was minimal or absent. Lactose and beta-methylgalactoside inhibited the destruction of the bacteria, whereas cellobiose and alpha-methylgalactoside were ineffective. Thus, the type 2 fimbriae of the oral actinomyces recognize galactose-containing receptors on polymorphonuclear leukocytes which have been exposed by the removal of sialic acid, an interaction that is followed by internalization and subsequent killing of the bacteria.